Concomitant dysregulation of microRNAs miR‐151‐3p and miR‐126 correlates with improved survival in resected cholangiocarcinoma. Issue 4 (4th July 2012) - McNally, Megan E.; Collins, Amy; Wojcik, Sylwia E.; Liu, James; Henry, Jon C.; Jiang, Jinmai; Schmittgen, Thomas; Bloomston, Mark
Abstract Background: MicroRNAs (miRNAs) are small non‐coding genes which become dysregulated in cancer and may predict survival. The role of miRNAs in outcomes in cholangiocarcinoma (CC) has not been reported. Methods: RNA was extracted from 32 resected CCs along with adjacent uninvolved bile duct epithelium. A total of 43 miRNAs were quantified using NanoString™. Clinicopathologic characteristics and outcomes were captured and compared. Overall survival curves were created using the Kaplan–Meier method; factors, including miRNA expression, were compared by log‐rank, chi‐squared or Cox regression analyses. Results: Absolute expression of each miRNA was compared with overall survival after excluding perioperative deaths (n= 3). One upregulated (miR‐151‐3p; P= 0.003) and one downregulated (miR‐126; P= 0.023) miRNA in resected CC relative to adjacent normal bile duct epithelium correlated with survival on univariate analysis. Clinical factors and these miRNAs were compared. Dysregulated miR‐151‐3p and miR‐126, respectively, were the only factors that correlated with improved overall survival [41.5 months vs. 12.3 months (P= 0.002) and 21.9 months vs. 15.1 months (P= 0.02), respectively]. In eight patients, both miRNAs were dysregulated. In the remainder, only one or neither showed dysregulation. Concomitant dysregulation correlated with the best overall survival (58.7 months vs. 15.1 months; P < 0.000; n= 8); clinicopathologic factors in these groups were otherwise similar. Conclusions: In resected CC, the concomitant dysregulation of both miR‐151‐3p and miR‐126 was the factor related to the greatest improvement in overall survival. Further analysis of the targets of these miRNAs may yield potential therapeutic targets or prognostic biomarkers.